Effect of recycled lime sludge, calcined clay and silica fume blended binder-based fibrous concrete with superior impact strength and fracture toughness - Murali G.; Katman H.Y.B.; Wong L.S.; Ibrahim M.R.; Ramkumar V.R.; Abid S.R. (Elsevier Ltd, 2024)
This study investigated the impact strength of fibrous concrete and its mode I, mode III, and mixed-mode I/III fracture toughness. Three binders were produced with varying compositions. The first binder was created by combining 95% clinker and 5% gypsum. The second binder consisted of 50% clinker, 30% calcined clay, 15% recycled lime sludge (RLS), and 5% gypsum. The third binder was composed of 50% clinker, 15% RLS, 30% silica fume, and 5% gypsum. There were three groups of binders used to classify the twelve different mixes. Each group comprises four different concrete mixtures: non-fibrous concrete, conventional fibrous concrete and two functionally graded fibrous concrete (FGFC) with three layers. Short-crimped steel fibres were utilized at an average dosage of 1.5% by volume. The fibre dosage of 2 and 2.25% was used in the top and bottom layers of FGFC and 0 and 0.5% were used in the middle. Besides, a microstructure study was performed to evaluate the strength development phases, utilizing X-ray diffraction, scanning electron microscopy, and thermogravimetric analysis techniques. Findings reveal that the mixture comprising an RLS and calcined clay binder combination exhibited the best compressive and impact strength performance. Introducing a three-layered concrete specimen with higher fibre content at the outer layer exhibits exceptional impact resistance compared to traditional fibrous concrete. Besides, fracture toughness under mode III is more critical than mode I and I/III and an increase in the load angle results in a reduced rate of improvement in fracture toughness. 2023 Elsevier Ltd